Analisis Kesalahan Pelafalan Fonem pada Akun Tiktok @Bachrul Alam ditinjau dari Maharah Kalam - Sayuti, Muhammad (Lisaanuna Ta`lim Al-Lughah Al-Arabiyah: Jurnal Pendidikan Bahasa Arab, 2024)
The development of the times makes it easier for us to learn and teach Arabic especially in maharah kalam by using social media such as tiktok. One of these tiktok accounts is @Bachrul Alam. On this account there are several language errors such as errors in pronouncing Arabic phonemes. This study to analyze and describe phoneme pronunciation errors this account. This research is a qualitative research with a case study type of research. The results of this study indicate that the phoneme pronunciation errors contained in the tiktok account are in the form of errors in pronouncing consonant sounds or letters thah have points of articulation and almost the same characteristics as ع ء ح ه ق ك س ث. This research is expected to reveal phoneme pronunciation errors in several videos that are identified as making language errors in phoneme pronunciation and become material for further consideration for Arabic language teachers to pay attention to every word spoken from Arabic in order to maintain the validity of Arabic itself.